Management of the Libidinal Impulses in Adolescents to Improve their Quality of Life - PARUL AGRAWAL; PRANAV PANDYA (Dr. Chinmay Pandya, 2015)
Aim of the present study was to examine the effect of yogic practices in managing libidinal impulses among adolescents and improving their quality of life. Experimental and control group design was used. Eighty samples were collected through accidental sampling (40 in experimental group and 40 in control group) from Mother Teresa Public School, Delhi. The students those who had high levels of libidinal impulses were selected. The age of the subjects ranged from 14-19 years. The students in the experimental group were made to do yogic practices regularly for 40 days. Libidinal Impulses Scale and PGI General Wellbeing Scale were used. The obtained values of t-test for Libidinal Impulses and General Wellbeing are significant at 0.01 level of confidence. The  result  of  the  study  shows  that  yogic practices  are  significantly  effective  in  reducing  the  levels  of  libidinal impulses  and  improve the level of quality of life of adolescents.